CO-DEVELOPMENT OF FIRM FOUNDINGS AND REGIONAL CLUSTERS - Dirk Fornahl; Max-Peter Menzel (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2003)
Although firm foundings and the formation of regional clusters are two processes that have separately attracted a lot of scientific attention during recent years, not much research has been conducted to analyse the interrelation between these two processes. This paper gives some new insights into this relation and a framework is presented into which empirical observations and theoretical considerations can be placed. The core elements are the effects the two processes have on each other in the different stages of cluster formation and development. – – Obwohl Firmengründungen und die Entstehung von regionalen Clustern in den letzten Jahren viel wissenschaftliche Aufmerksamkeit auf sich gezogen haben, wurde der Zusammenhang dieser beiden Prozesse bisher kaum analysiert. Dieses Papier stellt neue Erkenntnisse bezüglich dieses Zusammenhangs vor und präsentiert einen analytischen Rahmen, in den empirische Beobachtungen und theoretische Betrachtungen integriert werden können. Die Kernelemente sind dabei die Effekte, die die beiden Prozesse in den unterschiedlichen Phasen der Clusterentstehung aufeinander haben.
Keywords: D83; R12; M13; L21; 330; Firm founding; regional clusters; knowledge trajectories; distribution of regional economic activity; Unternehmensgründung; Regionale Konzentration